Mechanical, thermal, viscoelastic, and electrical performance evaluation of graphene nanoplatelets/polylactic acid (GNP/PLA) nanocomposites - Siddiqui, Vasi Uddin; Sapuan, S. M.; Mohd Ariffin, Mohd Khairol Anuar; Hassan, Mohd Roshdi (SpringerOpen, 2025)
Carbon materials have been prominent in the realm of composite materials due to their expansive surface area, exceptional strength, and tunability, making them suitable for various applications ranging from electronics to pharmaceuticals. Graphene nanoplatelets (GNPs) were incorporated into a polylactic acid (PLA) matrix using melt blending followed by a compression molding technique in this study to explore the mechanical, thermal, viscoelastic, and electrical properties of the resulting nanocomposites. Thorough mixing of various loadings (1, 3, 5, 8, and 12 PHR) of GNP with PLA was achieved using extrusion. Results demonstrate the improved mechanical, thermal, and electrical properties of introducing the GNP. Samples with low GNP loadings (1–3 PHR) exhibited improved tensile strength, with a maximum of 26.64 MPa for the PG1 sample. Nevertheless, at higher GNP loadings, the mechanical and thermal properties showed a decreasing trend due to particle agglomeration. In contrast, electrical conductivity increased significantly at higher loadings, reaching a maximum of 2.82 × 10−4 S/cm for the PG12 sample. GNP/PLA nanocomposites offer a viable and more environmentally friendly alternative to glass fiber-reinforced polymer composites in several high-strength applications, including aerospace, automotive, and construction.